Functional Activities Questionnaire Items that Best Discriminate and Predict Progression from Clinically Normal to Mild Cognitive Impairment - A. Marshall, Gad; S. Zoller, Amy; Lorius, Natacha; E. Amariglio, Rebecca; J. Locascio, Joseph; A. Johnson, Keith; A. Sperling, Reisa; M. Rentz, Dorene; for the Alzheimer’s Disease Neuroimaging Initiative (Current Alzheimer Research, 2015)
Background: Impairment in instrumental activities of daily living (IADL) emerges in the transition from mild cognitive impairment (MCI) to Alzheimer’s disease (AD) dementia. Some IADL scales are sensitive to early deficits in MCI, but none have been validated for detecting subtle functional changes in clinically normal (CN) elderly at risk for AD. Methods: Data from 624 subjects participating in the Alzheimer’s Disease Neuroimaging Initiative and 524 subjects participating in the Massachusetts Alzheimer’s Disease Research Center, which are two large cohorts including CN elderly and MCI subjects, were used to determine which Functional Activities Questionnaire items best discriminate between and predict progression from CN to MCI. Results: We found that “Remembering appointments” and “assembling tax records” best discriminated between CN and MCI subjects, while worse performance on “paying attention and understanding a TV program”, “paying bills/balancing checkbook”, and “heating water and turning off the stove” predicted greater hazard of progressing from a diagnosis of CN to MCI. Conclusions: These results demonstrate that certain questions are especially sensitive in detecting the earliest functional changes in CN elderly at risk for AD. As the field moves toward earlier intervention in preclinical AD, it is important to determine which IADL changes can be detected at that stage and track decline over time.
Keywords: Activities of daily living